1997
DOI: 10.1007/s004410050801
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the stomatogastric neuropil of the crab, Cancer borealis, as revealed by modulator immunocytochemistry

Abstract: We used antibodies to a number of neuromodulatory substances, including serotonin, FLRF amide, red pigment-concentrating hormone, substance P, proctolin and cholecystokinin, to investigate the distribution of molecules similar to these substances in the stomatogastric ganglion of the crab, Cancer borealis. No immunoreactivity was seen in the region of the cell bodies that surrounds the neuropil and little was found in the core of the neuropil (where the primary neurites of the intrinsic neurons occupy most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…of the M PNs, we were able to conclude that these neurons are not immunoreactive for serotonin or histamine (Beltz et al, 1984;Katz et al, 1989;Christie, 1995) or TN RN FLRFamide, CabTRP Ia, red pigment-concentrating hormone-like, allatostatin-like, buccalin-like, myomodulin-like, or cholecystokinin-like peptides Goldberg et al, 1988;Nusbaum and Marder, 1988;Christie et al, 1994Christie et al, , 1995Christie et al, , 1997cSkiebe and Schneider, 1994).…”
Section: Mpn Cotransmitter Complementmentioning
confidence: 89%
See 2 more Smart Citations
“…of the M PNs, we were able to conclude that these neurons are not immunoreactive for serotonin or histamine (Beltz et al, 1984;Katz et al, 1989;Christie, 1995) or TN RN FLRFamide, CabTRP Ia, red pigment-concentrating hormone-like, allatostatin-like, buccalin-like, myomodulin-like, or cholecystokinin-like peptides Goldberg et al, 1988;Nusbaum and Marder, 1988;Christie et al, 1994Christie et al, , 1995Christie et al, , 1997cSkiebe and Schneider, 1994).…”
Section: Mpn Cotransmitter Complementmentioning
confidence: 89%
“…We also paired intracellular LY fills of MCN1 SNAX with FMRFamide immunocytochemistry and determined that MCN1 SNAX is not FMRFamide immunoreactive (n ϭ 4). Christie et al (1997c) demonstrated that MCN1 SNAX also exhibits no cholecystokinin-like immunoreactivity. MCN1 SNAX is not serotonergic, because all of the serotonin (5-HT) immunoreactivity within the crab STG arises from the arbors of identified sensory neurons (Katz et al, 1989).…”
Section: Mcn1 Cotransmitter Complementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although extensive neuroanatomical and immunocytochemical work has demonstrated complex and rich patterns of colocalization for amines and peptides, how these substances modulate specific functional circuits remains relatively unknown. The stomatogastric nervous system contains ϳ20 different identified modulatory substances (Marder and Weimann, 1992;Marder et al, 1995;Christie et al, 1997a;Abbott and Marder, 1998), each of which can alter the STG motor patterns. The effects of serotonin (Kiehn and HarrisWarrick, 1992a,b;Zhang and Harris-Warrick, 1995), dopamine (Harris-Warrick et al, 1995a,b;Kloppenburg et al, 1999), and the peptide proctolin (Golowasch and Marder, 1992) have been characterized, but until now, the biophysical actions of most of the modulatory substances found in inputs to the STG were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It was purified based on its myotropic actions on the insect hindgut, and was subsequently found to have wide distribution throughout the arthropods (2)(3)(4). In the crab Cancer, proctolin has potent effects on defined neural circuits within the stomatogastric system (5) and at the neuromuscular junction (6).…”
mentioning
confidence: 99%